Methods of nutrition assessment in patients with head and neck cancer - Małecka-Massalska, Teresa; Chara, Krzysztof; Gołębiowski, Paweł; Władysiuk, Magdalena; Lupa-Zatwarnicka, Krystyna (Polish Journal of Public Health, 2013)
The head and neck tumors constitute large and complex group. The incidence of malnutrition in patients with head and neck tumors averages from 65 to 75%. That gives them the third place behind the pancreas and stomach tumors. The correct assessment of nutrition helps to recognize the degree of malnutrition and has influence on nutrition care and therapy. The dietary interview, anthropometric methods, bioimpedance and labolatory tests are used in evaluation of nutritional state in various scale. The degree of malnutrition has an influence on number of complications and extends the period of hospitalization, thus the methods evaluating the nutrition are commonly used in clinical practice.The objective of this article is to introduce the readers to the methods of nutrition assessment in patients with head and neck cancer.